Limitations and obstacles on wood identification from sculptures - analysis of a set of gilded and polychromed flemish artworks from the 15th century - Silva, José Luis (2021)
Wood identification through its internal anatomy is a complex and time-consuming process, often leading to taxonomic results at genus level (sometimes only family). The identification of the wood support of artworks contains specific methodological requirements and various limitations that are normally not applied with the common histological methodology. Preparation of wood for microscopic examination requires samples with approximately 1 cm3. This is a volume that can conflict with ethical issues of intervention, namely the scale of the piece itself, the aesthetic and structural integrity or even the commercial value of the artwork. Because of these, besides other factors such as the presence of metal leaf, polychromies and varnishes, collecting usually becomes impractical. Also, the absence of any crack, fracture or perforation where collecting could be facilitated, or the presence of degraded or already intervened areas allowed for collecting, all contribute to hamper the identification of wooden artworks. In this paper, which is intended mainly for artwork restorers, we describe the alternatives and solutions that were explored to circumvent the limitations on the wood processing for identification, which allowed us to analyse and characterize a set of Flemish 15th century polychromed and gilded sculptures.